2015
DOI: 10.1021/acs.jpca.5b01124
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Based Analysis of Photoinduced Electron Transfer in a Triazacryptand Based K+ Sensor

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. The electronic structure and photoinduced electron transfer processes in a K + fluorescent sensor that comprises a 4-amino-naphthalimide derived fluorophore with a triazacryptand ligand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 44 publications
1
63
0
Order By: Relevance
“…13 This interaction can lead to a series of transduction mechanisms that need to be understood to achieve efficiency and selectivity in the sensors. The most frequent sensing mechanisms shown by shown are Photoinduced Electron Transfer (PET), 14,15 intramolecular charge transfer (ICT), 9 Energy Transfer (ET), 14,16 Metal-Ligand Charge Transfer (MLCT or LMCT), 17 Excited State Intramolecular Proton Transfer (ESIPT), 18 excimer and exciplex formation. 19,20 The Schiff bases have been widely studied because of their biological and structural importance, mainly for their specic and selective reactions with metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…13 This interaction can lead to a series of transduction mechanisms that need to be understood to achieve efficiency and selectivity in the sensors. The most frequent sensing mechanisms shown by shown are Photoinduced Electron Transfer (PET), 14,15 intramolecular charge transfer (ICT), 9 Energy Transfer (ET), 14,16 Metal-Ligand Charge Transfer (MLCT or LMCT), 17 Excited State Intramolecular Proton Transfer (ESIPT), 18 excimer and exciplex formation. 19,20 The Schiff bases have been widely studied because of their biological and structural importance, mainly for their specic and selective reactions with metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…With this perspective in mind, we have extended the capabilities of the code by coupling it to a single-determinant DFT description of the excited states based on the ∆SCF approach, 40 which carries no extra computational cost with respect to ground-state DFT. ∆SCF is gaining increasing popularity in the study of the excited states of both organic chromophores [41][42][43][44] and transition metal complexes. 45,46 This renewed interest is motivated in part by the growing demand for computationally cheap strategies for simulating with sufficient accuracy the excited-state structure and dynamics of large systems, for which high-level multireference methods are not yet a viable choice.…”
Section: Introductionmentioning
confidence: 99%
“…requires excited state electronic structure methods, including structural optimization of the relevant states. This is commonly done using methods such as single excitation configuration interaction (CIS) or TDDFT . The study of large biological systems is challenging, as the size of the system usually precludes a full treatment with quantum chemical methods, necessitating some further approximations.…”
Section: Introductionmentioning
confidence: 99%
“…This is commonly done using methods such as single excitation configuration interaction (CIS) or TDDFT. [19,[33][34][35][36][37][38][39] The study of large biological systems is challenging, as the size of the system usually precludes a full treatment with quantum chemical methods, necessitating some further approximations. Despite this inherent complexity, several studies have reported calculations of ET in proteins based on Marcus theory.…”
Section: Introductionmentioning
confidence: 99%